2021
DOI: 10.1088/1361-6463/abde67
|View full text |Cite
|
Sign up to set email alerts
|

Operando characterisation of alumina-supported bimetallic Pd–Pt catalysts during methane oxidation in dry and wet conditions

Abstract: Near ambient pressure x-ray photoelectron spectroscopy (NAP-XPS) was used to study the chemical states of a range of alumina-supported monometallic Pd and bimetallic Pd-Pt nanocatalysts, under methane oxidation conditions. It has been suggested before that for optimal complete methane oxidation, palladium needs to be in an oxidised state. These experiments, combining NAP-XPS with a broad range of characterisation techniques, demonstrate a clear link between Pt presence, Pd oxidation, and catalyst activity unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…By in situ XAFS, the evolution of a bimetallic PtPd catalyst was followed, assessing its higher stability against sintering compared to a Pd-only sample thanks to the formation of a core-shell structure 25 . A recent near ambient pressure X-ray photoelectron spectroscopy (AP-XPS) study has shown that, under lean conditions, Pd tends to be fully oxidized making less clear the contribution of platinum on the catalytic activity in comparison to the behavior under stoichiometric conditions, where the bimetallic catalyst shows lower light-off temperature ascribed to the coexistence of Pd 2+ and Pd 0 promoted by the presence of Pt 26 . Previously, by in situ XPS, it was determined that the surface fraction of Pd 2+ depended on Pt content 27 .…”
Section: Introductionmentioning
confidence: 99%
“…By in situ XAFS, the evolution of a bimetallic PtPd catalyst was followed, assessing its higher stability against sintering compared to a Pd-only sample thanks to the formation of a core-shell structure 25 . A recent near ambient pressure X-ray photoelectron spectroscopy (AP-XPS) study has shown that, under lean conditions, Pd tends to be fully oxidized making less clear the contribution of platinum on the catalytic activity in comparison to the behavior under stoichiometric conditions, where the bimetallic catalyst shows lower light-off temperature ascribed to the coexistence of Pd 2+ and Pd 0 promoted by the presence of Pt 26 . Previously, by in situ XPS, it was determined that the surface fraction of Pd 2+ depended on Pt content 27 .…”
Section: Introductionmentioning
confidence: 99%
“…The ratios were selected to match previously tested nanoparticle catalysts of the same compositions. 12 Measurements in multiple positions (with spot size of 0.1 mm  0.1 mm) on individual samples suggest the composition was uniform across the samples both pre-and post-testing. 35 Samples were cut, with 5  3 mm (AE1 mm) pieces used for the experiments described below.…”
Section: Methodsmentioning
confidence: 97%
“…Nanoparticles for these reactions from our previous work typically had diameters of 1–10 nm, and were supported on alumina grains which are around 100 μm. 12 The lack of support material could also limit the extent to the deactivation seen in wet conditions, due to prior studies showing migration of hydroxyls from the support to the metal. 33…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations